2021
DOI: 10.1002/aenm.202101880
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Covalent Organic Framework/Carbon Nanotube Composite as Li‐Ion Positive Electrode with Ultra‐High Rate Performance

Abstract: low specific capacity of 73 mAh g −1 at 500 mA g −1 in a Li-ion cell. However, the electrochemical performance was greatly enhanced by forming the tube-type core-shell structure of the composites (DAPQ-COFX). Using this approach, we achieved specific capacities of up to 162 mAh g −1 at 500 mA g −1 . By varying the composition of the DAPQ-COFX composite, it was found that DAPQ-COF50, which contained 50 wt% of CNT, exhibited the highest utilization of the redox-active sites (95%). Notably, the DAPQ-COF50 composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
83
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(99 citation statements)
references
References 49 publications
(85 reference statements)
6
83
0
1
Order By: Relevance
“…Encouragingly, the C=O bond feature reforms when the electrode is recharged, and the spectrum of the charge electrode appears almost identical to that of the pristine electrode. This observation, consistent with our earlier work on the analogous 2-carbonyl 9,10-phenanthrequinone-based COF, 26 supports that the reversible charge storage involves the redox electrochemistry of the carbonyl (C=O) of the DAPT structure. For the 4-carbonyl containing PT-COFX composite materials, the earlier CVs ( Figure 2 a) indicate two prominent reaction peaks separated by ca.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…Encouragingly, the C=O bond feature reforms when the electrode is recharged, and the spectrum of the charge electrode appears almost identical to that of the pristine electrode. This observation, consistent with our earlier work on the analogous 2-carbonyl 9,10-phenanthrequinone-based COF, 26 supports that the reversible charge storage involves the redox electrochemistry of the carbonyl (C=O) of the DAPT structure. For the 4-carbonyl containing PT-COFX composite materials, the earlier CVs ( Figure 2 a) indicate two prominent reaction peaks separated by ca.…”
Section: Resultssupporting
confidence: 91%
“…As shown in Table S4 , the capacity of PT-COF50 outperforms that of other related COF-based composite cathodes. 12 14 , 16 , 17 , 26 , 32 , 33 , 36 , 37 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[15,18,27,39,16] New peaks COLi and LiO centered at 1387 and 1060 cm −1 appeared, respectively, which is mainly attributed to the lithiation of CO and the formation of SEI films. [40][41][42] It is demonstrated that the insertion of Li + into CO results in the formation of COLi bond. [43] In addition, a small peak of sp 2 -hybridized carbon (1500-1400 cm −1 ) appeared in such initial discharging process.…”
Section: Ex Situ Spectroscopic Characterizations Of Redox Reactions O...mentioning
confidence: 99%